Lipases and Their Functionality in the Production of Wheat‐Based Food Systems. Issue 5 (September 2014) - Gerits, Lien R.; Pareyt, Bram; Decamps, Karolien; Delcour, Jan A.
Abstract In the last several decades, food industries have increasingly used lipases as a result of the functional versatility of these enzymes and their potential beneficial effects in terms of processing and product quality. This review article discusses lipases and their functional effects during cereal‐based food processing with a focus on the production of bread and cakes. Their dough and batter intermediates, respectively, are essentially semi‐solid foams that upon baking are converted into solid cellular sponges. In both cases, the lipid fraction(s) from wheat (in the case of bread and cake), egg and/or bakery fat (in the case of cake) exert major roles in gas incorporation and stabilization in the cited semi‐solid foams. An up‐to‐date overview on the (potential) substrates, the different lipase enzymes, their action mechanism, their functionality, and how they impact bread and cake quality is presented. We also hypothesize on how the observed effects can be interpreted in terms of the altered lipid chemistry.